Exploring support for medicalized female genital mutilation/cutting: A study on migrant women living in Italy - Livia Elisa Ortensi; Patrizia Farina; Daniela Carrillo; Enrico Ripamonti (PLoS ONE, 2025)
The medicalization of female genital mutilation/cutting (FGM/C) as a harm reduction strategy is a highly debated issue, although largely unexplored among migrants living outside practising countries. This study investigates the extent of the support for FGM/C conditioned on its medicalization among migrant women from FGM/C-practising countries residing in Italy, and the characteristics of women supporting the practice. Data are from a national survey on FGM/C conducted in Italy in 2016, covering a representative sample of 1,378 women aged 18 + who were born in Nigeria, Egypt, Eritrea, Senegal, Burkina Faso, Somalia, and Ivory Coast. A discrete choice framework and a multinomial probit choice model are adopted to analyze women’s preferences about FGM/C continuation and medicalization. Findings indicate that, compared with women who support the practice unconditionally, the requirement of medicalization correlates with higher educational level, age, being in a couple, and being from a country where FGM/C is more commonly medicalized. Perceived benefits linked to increased support for FGM/C medicalization include religious approval, better marriage prospects, cleanliness, and conformity to traditional cultural values. Our data show that higher education is a critical, but not unique, factor in understanding the support for FGM/C in its medicalized form.